The Farmers' perceptions of the incidence and severity of damage by the armyworm (Spodoptera frugiperda J.E. Smith) (Lepidoptera: Noctuidae) in Nyiragongo Territory - LUBUNGA KAPASA Balthazar; Basimine Lulemire Bienfait; Elias Semajeri Ladislas; Mubenga Kankonda Onésime; Basingere Bisimwa Espoir (Eastern Journal of Agricultural and Biological Sciences, 2024)
Abstract - In this study, Rusayo and Mudja present their knowledge, perceptions and management practices with regard to the armyworm (Spodoptera frugiperda). 120 farmers were interviewed. The majority of farmers in Rusayo and Mudja were familiar with the armyworm. They could generally identify it at the larval stage. In addition, the majority of farmers (89%) had suffered damage caused by the armyworm on their farms, resulting in an estimated yield reduction of between 0.1 and 3 tonnes per hectare. More than half of the farmers used chemical insecticides to combat the pest. A majority of 60% of farmers considered that insecticides were not effective in combating the armyworm. Key words : Perception, Incidence, Severity, Spodoptera frugiperda, Maize, Damage